Nosemosis in Honeybees: A Review Guide on Biology and Diagnostic Methods - Ewa Danuta Mazur; Anna Maria Gajda (Applied Sciences, 2022)
Nosema apis and Nosema ceranae are dangerous parasites of the honey bee (Apis mellifera). N. ceranae is more pathogenic and, nowadays, more widespread than N. apis. There are also cases of mixed infections or infections of only N. apis. Both N. apis and N. ceranae can lead to the weakening or death of A. mellifera colonies. It is crucial to make a fast and reliable diagnosis to monitor the disease and to start the correct treatment. Additionally, there is a need for further research on the pathogenicity of Nosema spp. and also on their prevalence in different regions of the world. In this paper, we present reliable diagnostic methods for Nosema spp. infection in honey bees and list the advantages and disadvantages of each method. We have also included basic information about nosemosis and the majority of diagnostic methods in order to provide a source of knowledge for veterinarians and researchers.